George Perkovich and Toby Dalton, Not War: Not Peace? Motivating Pakistan to Prevent Cross-Border terrorism - Mr. Majid Mahmood (CISS Insight Journal, 2016)
The book titled “Not War, Not Peace? Motivating Pakistan to Prevent CrossBorder terrorism” co-authored by George Perkovich and Toby Dalton is a thorough analysis of policy options available to India and their feasibility in dealing with cross border terrorism generating from Pakistan. The book is also about how Indian calibration of the policy options may motivate or compel Pakistani policy makers to end their proxy war against India. The title of the book “Not War, Not Peace?” describes the complex relationship between Pakistan and India, two nuclear armed rivals, as it exists today. In the authors’ perceptions, limited wars under nuclear overhang and coercive compellence, instead of give and take bargaining, are very much part of policy milieu in India and Pakistan. Will these policies achieve their desired objectives is what the question mark in the title suggests. The authors have taken a position in the title about Pakistan being a source of terrorism inside India which reads “Motivating Pakistan to Prevent Cross-Border terrorism” and have built the argument forward from this baseline.The book contains six chapters each detailing a single policy option available to India. The chapters link up with the broader theme of book’s title “Motivating Pakistan to Prevent Cross-Border terrorism”. The cost benefit analysis and issues related to real Indian capabilities, as opposed to projected capabilities, to achieve policy ends vis a vis Pakistan are succinctly analyzed in each chapter. The authors conclude that an appropriate mixture of violent and non- violent strategies coupled with domestic Indian reforms in defense and intelligence sector will enable India to address its most important foreign policy challenge: Pakistan.